Motivation to teach and preparedness for teaching among preservice teachers in China: The effect of conscientiousness and constructivist teaching beliefs - Huang, JiaLi; Sang, Guoyuan; He, Wenjie (Frontiers in Psychology, 2023)
“Preparedness for teaching” refers to the degree of confidence preservice teachers have, and reflects their ability. Developing preparedness for teaching is an important part of preservice teachers’ professionalization. A substantial body of literature has documented the critical influence of the motivation to teach on preparedness; however, how this relation is impacted by mediating and moderating mechanisms remains unclear. To respond to this gap in knowledge, the present study constructed a mediated moderation model through structural equation modeling and multigroup tests using 383 questionnaires completed by preservice teachers in China. The findings indicate that the preservice teachers’ genders, entry path, and levels of certainty about their future teaching career choices all influence their preparedness for teaching. Specifically, preservice teachers who believe that they will choose a teaching career in the future have more intrinsic motivation, stronger constructivist teaching beliefs, and a higher levels of teaching preparedness. Moreover, preservice teachers’ motivations to teach can positively predict their constructivist teaching beliefs and preparedness for teaching, but their constructivist teaching beliefs alone do not have a mediating effect on the relationship between motivation to teach and preparedness for teaching. However, the findings reveal that the constructivist teaching beliefs of highly conscientiousness group can partially mediate the relationship between the motivation to teach and the preparedness for teaching. Additionally, conscientiousness moderates the influence of constructivist teaching beliefs on preparedness for teaching. The study provides meaningful insights into the within-personal traits of how and when motivation to teach affects preparedness for teaching, which may be useful for the motivation best practices for preservice teacher recruitment, training, and support to create high-quality teachers.